SOIL MACROFAUNA COMMUNITY IN RECLAMATION AREA OF GOLD MINING-BATU HIJAU PROJECT, WEST SUMBAWA, WEST NUSA TENGGARA - Hastuti, Feni
The main problem that arises in ex-mining site area is chemical, physical and biological environmental changes. Reclamation activities is expected to produce better situation than before. Soil macrofauna plays an important role in the reconstruction of ecosystem functions as an ecosystem engineer. This study aims to examine the soil macrofauna community structure and environmental conditions in several reclamation areas, and natural forests. The study was conducted in the reclamation area of 1, 4, 7, 11, 13 years and natural forests of the Batu Hijau Project, West Sumbawa, West Nusa Tenggara. Sampling of Arthropoda group is done by pitfall traps, three plots are installed with three repetition series in the period of time from January to March 2019. Sampling of Oligochaeta group is done at each point (30x30cm and 15cm depth) using the hand sorting method and then it was identified, also its biomass is being weighed. The parameters of environmental conditions measured include soil moisture, soil pH, soil temperature, water content, percentage of mineral and organic content, bulk density, porosity, C/N ratio, air temperature, air humidity, canopy cover, and litter biomass measurements were carried out on three points in each area. The total results of Arthropod individuals found were 7117 individuals, which included 152 species, 66 families, 15 orders, and 5 classes with Formicidae found most (75.88%). Species richness (S), species evenness (E), and diversity index (H') from Arthropods were found in the lowest value at 1 years reclamation (S: 37; E: 0.15; H': 0.56) and the highest at 13 years (S: 47; E: 0.52; H': 1.99) while dominance (D) only occurs in the 1 year reclamation area (D: 0.84). The results of the finding of soil macrofauna Oligochaeta group found three species, Pheretima sp., Lumbricus rubellus, Lumbricus terrestris, with the highest species richness were found in 13 years reclamation area and natural forests (S:3) and the highest biomass were found in natural forest (46.31gr/cm2). As the age of reclamation increases, the level of species diversity and species evenness is higher and the absence of dominance of soil macrofauna are found. This is supported by environmental conditions in reclamation areas that are getting older and having similarities with natural forests.